Evaluation of TNF-α Concentration Level in Al-Najaf Hospitals Patients Infected with Hydatid Cysts - Sayal, Raad Ajam; Mohammed, Haider Malik (Newinera Publisher, 2024)
Human echinococcosis is a zoonotic disease caused by a species of medical importance, the Echinococcus granulosus , an etiological agent of cystic echinococcosis (CE). A radiological examination will be performed for these patients to diagnose Echinococcus granulosus parasite by find echinococcal cysts. All of these patients were involved in this study and during the period starting from October 2023 to the end of January 2024, from all ages of patient from both sex (Males and Females At Al-Sader Medical City, AL-Hakeem General Hospital, AL-Haidarya general Hospital and Al-Hayat Hospital. The mean level of TNF-α in patients is 163.27 pg/ml, which is significantly higher than the mean level of 38.58 pg/ml in controls (p-value < 0.001). The prevalence of hydatid disease in Al-Najaf Al-Ashraf in this study was 33%. Levels of the cytokines IL-6, TNF-α, IL-1ß, and IL-4 are more important in patients with Echinococcus granulosus under 40 years of age than in those over 40 years of age.